Permodelan Enterprise Resource Planing Pada TB Muncul Agung - Nuranisa, Siti; Nopiana, Medi (Jurnal Ilmiah Wahana Pendidikan, 2024)
Hardware, paint, other building products, and glass are all sold in specialty shops and retail trade by TB Muncul Agung. Currently, the system at TB Muncul Agung manages the manual (traditional) buying and selling procedure. During the process of verifying stock, this condition frequently arises. The lack of organization in the information on the placement of the merchandise is another issue that exists in TB Muncul Agung. This scenario creates issues in the form of erroneous stock data and product position information, which costs the organization money. Due of this, information modeling was used in this study to define the requirements of both purchasing and selling. The enterprise resource planning (ERP) created as a result of the modeling is implemented using the Odoo application. The results of the implementation demonstrate that Odoo may be used for UML modeling and implementation as required. Odoo provides a wide range of integrated modules, including modules for customer administration, accounting, sales, and even purchasing